2001
DOI: 10.1523/jneurosci.21-19-07517.2001
|View full text |Cite
|
Sign up to set email alerts
|

Contactin Associates with Na+Channels and Increases Their Functional Expression

Abstract: Contactin (also known as F3, F11) is a surface glycoprotein that has significant homology with the beta2 subunit of voltage-gated Na(+) channels. Contactin and Na(+) channels can be reciprocally coimmunoprecipitated from brain homogenates, indicating association within a complex. Cells cotransfected with Na(+) channel Na(v)1.2alpha and beta1 subunits and contactin have threefold to fourfold higher peak Na(+) currents than cells with Na(v)1.2alpha alone, Na(v)1.2/beta1, Na(v)1.2/contactin, or Na(v)1.2/beta1/bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
182
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 172 publications
(189 citation statements)
references
References 46 publications
6
182
1
Order By: Relevance
“…Sodium channels are clustered at high density in axon initial segments and nodes of Ranvier of myelinated axons, where they co-localize with members of the Ig superfamily of CAMs such as contactin, NrCAM, and neurofascin 186 (Nf186) (2,17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium channels are clustered at high density in axon initial segments and nodes of Ranvier of myelinated axons, where they co-localize with members of the Ig superfamily of CAMs such as contactin, NrCAM, and neurofascin 186 (Nf186) (2,17,18).…”
mentioning
confidence: 99%
“…␤1 and ␤2 colocalize with sodium channel ␣ subunits at nodes of Ranvier, and ␤1 interacts with contactin and with Nf186 in vitro (9,17,19,20). Nf186, Nr-CAM, ␤1, and ␤2 each interact in vitro with a key cytoskeletal anchoring protein, ankyrin G , that is also localized to nodes of Ranvier (21)(22)(23).…”
mentioning
confidence: 99%
“…Auxiliary ␤-subunits affect the assembly, trafficking, and electrophysiological activities of ␣-subunits (6) and have recently been shown to link sodium channels to extracellular matrix proteins via their association with neurofascin (7). The neuronal adhesion molecule contactin/F3 increases the membrane insertion of sodium channels by direct (8) or indirect (9) association with the ␣-subunit of the channels. The association with contactin/F3 may also mediate the interaction of the channel with the extracellular protein tenascin (8).…”
mentioning
confidence: 99%
“…13,14 F3 is the first GPI-linked molecule identified that is located in both nodal and paranodal regions. 15,16 It forms an intracellular complex with paranodin, a single transmembrane protein 17 also termed Caspr and modulates its transfer from the endomembrane system to the axolemma. 15,18 F3 also is clustered at the paranode, a critical site of axoglial dialog for initiating myelination, from the first postnatal week.…”
Section: Discussionmentioning
confidence: 99%
“…15,18 F3 also is clustered at the paranode, a critical site of axoglial dialog for initiating myelination, from the first postnatal week. 16 PTPα interacts with F3 to form a membrane-spanning co-receptor complex, which potentially transduces extracellular signals. 7 Similar to F3, PTPα is expressed by both neuron and oligodendrocytes in the CNS.…”
Section: Discussionmentioning
confidence: 99%